EKSISTENSI BAHASA DALAM REALITAS PEMBANGUNAN BANGSA: SEBUAH KAJIAN - Christina Purwanti (PARAPOLITIKA: Journal of Politics and Democracy Studies, 2021)
The existence of language in the reality of nation building is always interesting to study. Language, either directly or indirectly, contributes to the social life of the nation and contributes to the development of the nation through character building. Through language, language users can convey their thoughts clearly and all their thoughts can be identified correctly: the exact meaning, value and purpose of the language. The meaning, value and purpose of language are not neutral in every use in various realities of social life. In this context, language users should be responsible for the meaning of the language used in various social environments in a nation. The aspect of language or the existence of language can be said to be a spiritual element that is always inherent in itself and has always been an important part in nation building, especially the development of the character of language users. In writing this article the author uses a qualitative method with an interdisciplinary approach. This article contains a study of how the existence of language becomes a very important part in nation building.